National Security Perspectives on Terrorism Risk Insurance in the United States - Willis, Henry H. (RAND Corporation, 2014)
Congress enacted the Terrorism Risk Insurance Act (TRIA) in 2002, in response to terrorism insurance becoming unavailable or extremely costly in the wake of the 9/11 attacks. TRIA is set to expire at the end of 2014, and Congress is considering the appropriate government role in terrorism insurance markets. This policy brief examines the potential national security implications of allowing TRIA to expire.